A case of pancreatic adenosquamous cell carcinoma with a pseudocyst following curative surgery - Nao Kitasaki; Tomoyuki Abe; Masashi Inoue; Marino Teshima; Masataka Nakagawa; Masatoshi Kochi; Ryuichi Hotta; Kazuhiro Toyota (Surgical Case Reports, 2024)
Abstract Background Pancreatic adenosquamous cell carcinoma (PASC) is a relatively rare histological type of pancreatic malignancy, and preoperative diagnosis is difficult because of its rarity. PASC accounts for 1–4% of all pancreatic cancers, and even after curative surgery, its prognosis is poorer than that of ordinary pancreatic adenocarcinoma. Pathologically, it shows glandular and squamous differentiation of cells. Complete resection is the only method to achieve a good long-term prognosis, and an increasing doubling time of PASC is considered to indicate early recurrence after surgery. Here, we report a rare case of PASC with an infected pancreatic cyst that was difficult to treat, along with a review of the literature. Case presentation A woman in her 80s with a history of breast cancer presented with pericardial pain. Computed tomography revealed a 20-mm hypovascular tumor in the body of the pancreas and a 27-mm pseudocyst. Endoscopic retrograde cholangiopancreatography showed a severe main pancreatic duct stenosis in the body of the pancreas that made cannulation impossible, and contrast media extravasation was due to pancreatic duct disruption in the pancreatic tail. Endoscopic fine-needle aspiration revealed that the tumor was a PASC. Because the patient had an infected pancreatic cyst, central intravenous nutrition and antibiotics were administered, which stabilized her general condition. She was diagnosed with resectable PASC and underwent distal pancreatectomy with lymphadenectomy. The postoperative course was uneventful. Immunohistochemical analysis of the resected specimen confirmed T2N0M0 stage IB. Systemic adjuvant chemotherapy with S-1 is ongoing. Conclusion Appropriate preoperative management and preoperative accurate staging (T2N0M0 stage IB) of PASC with curative surgery can ensure predictable outcomes.